Temperature dependence uptake of gold nanoparticles into pancreas cancer cells - Trono, Jade Dungao (Animo Repository, 2010)
Gold nanoparticles intracellular uptake was investigated using human pancreas cancer cells. Cell viability at different concentration, incubation time and incubation temperature was measured using MTT assay. Cellular uptake of gold nanoparticles was analyzed using Atomic Absorption Spectrometry (AAS). It was found that the viability of pancreas cancer cells is not significantly affected by the gold nanoparticles concentration and incubation time, indicating that gold nanoparticles are not toxic to cells. Also, the uptake of gold nanoparticles was not affected by small temperature difference. These findings of this study will help in the optimization conditions suitable for nanoparticles uptake for therapeutic and diagnostic applications of gold nanoparticles in the X-ray Drug Delivery System.